2014
DOI: 10.1111/gcb.12364
|View full text |Cite
|
Sign up to set email alerts
|

Modeling daily flowering probabilities: expected impact of climate change on Japanese cherry phenology

Abstract: Understanding the drivers of phenological events is vital for forecasting species' responses to climate change. We developed flexible Bayesian survival regression models to assess a 29-year, individual-level time series of flowering phenology from four taxa of Japanese cherry trees (Prunus spachiana, Prunus × yedoensis, Prunus jamasakura, and Prunus lannesiana), from the Tama Forest Cherry Preservation Garden in Hachioji, Japan. Our modeling framework used time-varying (chill and heat units) and time-invariant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…However, we argue that there are no relevant evidence to clearly elucidate the physiological mechanisms of the effect of chilling requirement on the first flowering time of cherry trees. In fact, the physiological mechanisms controlling bud burst and flowering of plants in early spring are not precisely known (Allen et al, 2014). Moreover, there is a flaming dispute on whether the effects of chilling accumulation and heat accumulation are overlapped in time (Allen et al, 2014;Chuine et al, 2016;Martínez-Lüscher et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, we argue that there are no relevant evidence to clearly elucidate the physiological mechanisms of the effect of chilling requirement on the first flowering time of cherry trees. In fact, the physiological mechanisms controlling bud burst and flowering of plants in early spring are not precisely known (Allen et al, 2014). Moreover, there is a flaming dispute on whether the effects of chilling accumulation and heat accumulation are overlapped in time (Allen et al, 2014;Chuine et al, 2016;Martínez-Lüscher et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Even in equatorial regions, oil palm is able to react to subtle variations in photoperiod and drought events by changing its bunch productivity (Legros et al 2009). Cherry tree phenology reacts promptly to climate, notably heat, with global warming expected to bring flowering a month forward (Allen et al 2014). Ismaili et al (2016) showed a significant genotype-byyear interaction in apricot tree, and recommend the use of mixed models for the analysis of perennial plants’ longitudinal data.…”
Section: Discussionmentioning
confidence: 99%
“…This type of survival model with time-dependent covariates has also been used in the medical sciences (Sen et al 2010). Recently, similar daily survival models were used to estimate the effects of forcing and chilling on cherry tree phenology (Terres et al 2013, Allen et al 2014. These studies show that, when critical parameters of mechanistic models are known or assumed (in particular, the threshold amount of chilling and the date of transition from chilling to forcing), survival models may offer a useful bridge between mechanistic and statistical models.…”
Section: Statistical Analysesmentioning
confidence: 99%